Characterization, Expression Profiling, and Functional Analysis of PtDef, a Defensin-Encoding Gene From Populus trichocarpa - Wei, Hui; Movahedi, Ali; Xu, Chen; Sun, Weibo; Wang, Pu; Li, Dawei; Yin, Tongming; Zhuge, Qiang (Frontiers in Microbiology, 2020)
PtDef cloned from Populus trichocarpa contained eight cysteine domains specific to defensins. Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) analysis showed that PtDef was expressed in all tissues tested, with lower expression in leaves and higher expression in petioles, stems, and roots. Purified fused PtDef inhibited Aspergillus niger, Alternaria Nees, Mucor corymbifer, Marssonina populi, Rhizopus sp., and Neurospora crassa. PtDef also inhibited the growth of Escherichia coli by triggering autolysis. PtDef overexpression in Nanlin895 poplar (Populus × euramericana cv. Nanlin895) enhanced the level of resistance to Septotinia populiperda. qRT-PCR analysis also showed that the expression of 13 genes related to salicylic acid (SA) and jasmonic acid (JA) signal transduction differed between transgenic and wild-type (WT) poplars before and after inoculation, and that PR1-1 (12–72 h), NPR1-2, TGA1, and MYC2-1 expression was higher in transgenic poplars than in WT. During the hypersensitivity response (HR), large amounts of H2O2 were produced by the poplar lines, particularly 12–24 h after inoculation; the rate and magnitude of the H2O2 concentration increase were greater in transgenic lines than in WT. Overall, our findings suggest that PtDef, a defensin-encoding gene of P. trichocarpa, could be used for genetic engineering of woody plants for enhanced disease resistance.